Pengaruh Pembiayaan Mudharabah Dan Musyarakah Terhadap Penurunan Profitabilitas Melalui Non Performing Financing - Eko Cahyo Mayndarto (Universitas Gorontalo, 2020)
The research aims to determine the influence of Mudharabah financing and musyarakah financing on reducing profitability (ROE) with non performing financing NPF) as an intervention variable in the Sharia Credit Bank (BPRS). This type of research is quantitative research with sharia Bank population in Indonesia period 2014-2018. Sampling selection is a random sampling method, and the analysis tools used are multiple regression analyses using SPSS tool version 22. Based on the results of road analysis test showed that the mudharabah and musyarakah variables did not significantly affect the profitability of the Sharia Bank Creditors. The mudharabah and musyarakah variables have no effect on the NPF. While the NPF is unable to increase mudharabah and musyarakah financing against the ROE.",